Methodological process in the construction of scales: Homelessness Prevention Scale - Giménez-Rodríguez, Silvia; Carbonero Muñoz, Domingo; Alcázar Ruiz, Rafael (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The present work presents the complete process for the creation of a scale. A scheme has been followed that encompasses the design process of a scale and its subsequent validation. For this, we focus on a case study that shows the development of a homelessness prevention scale related to the stressful life events that homeless people have experienced before the situation of homelessness, and from this, observe their inclusion difficulties.